Ulama dan Politik: Relasi Politik Tuan Guru Bajang pada Pemilu 2019 - Muh Arif Royyani; Tika Ifrida Takayasa (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2020)
Political contestation in the 2019 elections is not only about the contestation of political parties, but the involvement of the Tuan Guru and Ulama regarding ijtihad (political thought) is a concern. The use of Political Identity in the 2019 Elections is damaging to the integration of the nation and state of Indonesia. It began with the 2017 DKI regional election contestation with the start of a demonstration in the name of the defense of religion on December 12, 2016 to try Ahok who was considered blasphemous about religion. TGB is one of the figures who supported the demonstration so that it received sympathy from the alumni brotherhood of 212. PA 212 support was stopped when TGB opposed in supporting Jokowi in the 2019 Election. As Gunernur NTB, TGB had thought according to rational choice considerations in expressing its support for Joko Widodo. Rational choice through consideration of the benefit (goodness) of the people is a priority that encompasses all Indonesian people, including NTB.